Pesan Toleransi Dalam Dakwah Habib Husein Ja’far Al-Hadar Konten Youtube ‘LOGIN DI CLOSE THE DOOR’ - Siti Nur Afidah; Bobby Rachman Santoso (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
Over time, the types of media used to spread Islamic teachings have become increasingly diverse. Today, social media, particularly YouTube, has become extremely popular among the general public. YouTube offers an effective alternative for accessing information. However, the ease of accessing information also presents challenges, such as the limited ability of some Indonesian society to filter positive content. This can lead to issues like intolerance. In fact, the application of tolerance in Indonesian society can create a harmonious and mutually respectful life. During Ramadan 2023, content produced by Habib Ja'far and Onad suddenly became popular, especially because the interfaith discussions they presented strongly emphasized the value of tolerance without demeaning others. This study uses a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The data is divided into two types: primary, which consists of Habib Ja'far as the subject of his preaching, and secondary, which includes books, news, and literature related to tolerance preaching in Indonesia. The results of the study show that Habib Ja'far always emphasizes the value of tolerance in his preaching. His messages are delivered in a polite and respectful manner, with good communication skills, successfully attracting the attention of both Muslim and non-Muslim communities. These messages cover various da'wah topics, including knowledge about other religions and the importance of mutual respect and appreciation for differences. With a smart, loving, and relaxed approach, Habib Ja'far encourages his audience to strengthen interfaith relations and build an inclusive society.